Pengaruh Penggunaan Sistem Informasi Akuntansi E-Kasir Dan Keahlian Pemakai Terhadap Kualitas Laporan Keuangan Pada UMKM Di Provinsi Jawa Tengah - Fajar Romadhoni; Eskasari Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to examine the effect of implementing an E-cashier accounting information system and user expertise on the quality of financial reports for MSMEs in Central Java. The population used in this research is all MSMEs in Central Java, totaling 183,181 units in the first quarter of 2023. The data used in this research is primary data obtained directly from MSME actors. The research sampling technique used the purposive sampling method. The data analysis used is the Structural Equation Model (SEM). The findings of the empirical analysis show that the e-cashier accounting information system has a positive effect on the quality of MSME financial reports in Central Java province, while user knowledge and user skills have no effect on the quality of MSME financial reports in Central Java Province. Keywords: E-Cashier, Financial Reports, MSMEs